Super-resolution microscopy as a drug discovery tool - Lauren Toms; Lorna FitzPatrick; Philip Auckland (SLAS Discovery)
At the turn of the century a fundamental resolution barrier in fluorescence microscopy known as the diffraction limit was broken, giving rise to the field of super-resolution microscopy. Subsequent nanoscopic investigation with visible light revolutionised our understanding of how previously unknown molecular features give rise to the emergent behaviour of cells. It transpires that the devil is in these fine molecular details, and essential nanoscale processes were found everywhere researchers chose to look. Now, after nearly two decades, super-resolution microscopy has begun to address previously unmet challenges in the study of human disease and is poised to become a pivotal tool in drug discovery.